Systematic Review of Performance Optimization Techniques for Data Pipelines in High-Volume Cloud-Based Analytics Systems - Oluwademilade Aderemi Agboola,; Oyinomomo-emi Emmanuel Akpe,; Abraham Ayodeji Abayomi,; Jeffrey Chidera Ogeawuchi,; Toluwase Peter Gbenle,; Samuel Owoade, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In the era of data-driven decision-making, high-volume cloud-based analytics systems have become integral to organizations across various industries. Optimizing the performance of data pipelines in such systems is crucial to ensure efficient processing, scalability, and timely insights. This paper provides a systematic review of performance optimization techniques for data pipelines in cloud environments, focusing on key methods such as scalability, parallel processing, data streamlining, caching, and resource management. The review highlights the challenges that organizations face, including issues with data quality and integrity, system complexity, and the balance between performance improvements and associated costs. It further discusses the implications of these challenges for the effective management of cloud-based data pipelines and provides recommendations for overcoming them. The paper concludes with suggestions for future research in areas such as machine learning integration, intelligent caching, edge computing, and serverless computing. These findings offer valuable insights for professionals in cloud-based analytics, enabling them to enhance pipeline efficiency while managing operational costs effectively.
Keywords: Cloud-based analytics; Data pipeline optimization; Scalability; Parallel processing; Resource management; Performance challenges